(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
Advertising communication tends to shorten the use of the language means. This characteristic explains the deliberate usage of such linguistic constructions that primarily influence the potential consumer. The role of advertising has increased in the modern world. Its strengthening intensifies the interest in the study of this social phenomenon among the scientists in various fields. The relevance of the study is obvious due to the fact that the issues of verbal influence on the recipient remains unexplored in modern Ukrainian linguistics. The thesis identifies and examines the basic communicative pragmatic and stylistic parameters of Ukrainian text advertising, including the methods and the expressions of accentuations types. The important goal of advertising communication is to influence the recipient by means of the appellative language function. For implementing the commercial strategy copywriters actively use the speech and language techniques to appeal to a consumer and attract his attention to certain characteristics of the goods or services. Specific language functional and semantic categories such as addressing, accentuation, and evaluation provide the achievement of communicative pragmatic tasks in the advertising text. Accentuation in the advertising texts is quite effective communicative pragmatic means. Key words, accentual particles and modal words copywriters can effectively emphasize and highlight specific features of a product or service.